PENGARUH MOTIVASI, LINGKUNGAN KERJA DAN BUDAYA ORGANISASI TERHADAP PRODUKTIVITAS KERJA KARYAWAN PT. SURYA SAKTI UTAMA, SURABAYA - Pratiwi, Connie Dwi; Prabowo, Budi (Jurnal Bisnis Indonesia, 2019)
Human Resources have a very important role for success or benchmark for an organization or company, because humans are living assets that need to be considered specifically by a company or organization. PT. Surya Sakti Utama Surabaya is a footwear manufacturer. Based on the background above, the purpose of this study is to find out whether motivation, work environment and organizational culture have an influence simultaneously and partially to employee work productivity of employees at  PT. Surya Sakti Utama Surabaya. This type of research is quantitative research. This study uses primary data, namely data taken directly from the questionnaire (questionnaire) filled out by respondents. Population taken is a production department employee. The sample used was 100 employees in the production section of PT. Surya Sakti Utama Surabaya. The independent variables are motivation, work environment, and organizational culture, while the dependent variable is employee work productivity. To prove the hypothesis proposed, used Multiple Linear Regression Analysis and F Test, t Test Based on data analysis, it can be concluded that there are significant simultaneous influences between Motivation, Work Environment, and Organizational Culture on Employee Productivity. But for the Work Environment there is no partial effect on Employee Productivity, while Motivation andOrganizationalCulture partial effect on work productivity of employees. Keyword: Motivation, Work Environment and Organizational Culture on Work Productivity